Challenges for the beginners to hit the hegemony and anarchy - Alam, Gazi Mahabubul (2024)
These day, early-career academics face greater pressure to publish as a result of the dramatic shift in higher education, particularly in rising Asia, to compete in the international ranking league table and the race of scholars towards a metrics-driven culture of publication. They cannot sustainably or naturally nurture them due to these challenges. Publishing papers in the reputable journals that the western publishers support faces a challenge that is frequently referred to as “hegemony and anarchy”. Not only do academics from the west contribute to this atmosphere of hegemony and chaos, but elite academics from the east who follow western principles also influence. In these conditions, novices in developing soil frequently find it diFicult to publish. Nevertheless, the early-career researcher also lacks exposure, competency, and confidence when it comes to publishing. A new avenue for publication, known as “open access” provision, has been made available to respond to the continuous rise in demand for publications. The beginners try to publish in open access in the current context, but funding shortages are also a major worry. Because the authors provide the funding for open-access publications, the quality assurance system experiences criticism. For the novices, this has led to more severe hegemony and anarchy. The diFiculties that novices face will be emphasised in this keynote speech, along with some tactical recommendations for dealing with hegemony and anarchy without jeopardising the researcher's natural and sustainable development.